Dokumentation von küstennahem Auftrieb anhand stabiler Isotope in rezenten Foraminiferen vor Nordwest-Afrika - Ganssen, Gerald (Bornträger, 1983)
Foraminifera shells from modern sediments document the hydrography of the coastal upwelling region off Northwest-Africa (12-35° N) through the stable isotopic composition of their shells. Oxygen isotopes in planktonic foraminifers reflect sea-surface temperatures (SST) during the main growing season of the different species: Globigerinoides ruber (pink and white) and G. sacculifer delineate the temperatures of the summer, Globorotalia inflata and Pulleniatina obliquiloculata those of the winter. Oxygen isotopes in Globigerina bitlloides document temperature ranges of the upwelling seasons. δ18O values in planktonic foraminifera from plankton hauls resemble those from surface sediment samples, if the time of the plankton collection is identical with that of the main growing season of the species. The combined isotopic record of G. ruber (white) and G. inflata clearly reveals the latitudinal variations of the annual mean SST. The deviation of the δ18O values from both species from their common mean is a scale for the seasonality, i.e. the maximum temperature range within one year. Thus in the summer upwelling region (north of 25° N) seasonality is relatively low, while it becomes high in the winter upwelling region south of 20° N. Furthermore, the winter upwelling region is characterized by relatively high δ18O values - indicating low temperatures - in G. bulloides, the region of summer upwelling by relatively low δ18O values compared with the constructed annual mean SST. Generally, carbon isotopes from plankton hauls coincide with those from sediment surface samples. The encrichment of 13C isotopes in foraminifers from areas with high primary production can be caused by the removal of 12C from the total dissolved inorganic carbon during phytoplankton blooms. It is found thatcarbon isotopes from plankton hauls off Northwest-Africa are relatively enriched in 13C compared with samples from the western Atlantic Ocean. Also shells of G. ruber (pink and white) from upwelling regions are enriched in the heavy isotope ...